Micro-analytical uranium isotope and chemical investigations of zircon crystals from the Chernobyl ‘‘lava’’and their nuclear fuel inclusions - Pöml, P.; Burakov, B.; Geisler, T.; Walker, C.T.; Grange, Marion; Nemchin, Alexander; Berndt, J.; Fonseca, R.O.C.; Bottomley, P.D.W.; Hasnaoui, R. (Elsevier BV * North-Holland, 2013)
U isotope data measured on real fragments of the Chernobyl nuclear fuel included in zircon crystals crystallised from the Chernobyl “lava” are presented for the first time. The U isotope data show no anomalies and lie within the expected burnup values for the Chernobyl nuclear fuel. However, the U concentration, the U isotopic composition, and the Ti concentration in the host zircon vary significantly within single crystals as well as between single crystals. Our results indicate that during the time of melt activity temperature and melt composition likely varied considerably. New melt was formed progressively (and solidified) during the accident that reacted and mixed with pre-existing melt that never fully equilibrated. In such an environment zircon crystals crystallised at temperatures below 1250 °C, as estimated from thermodynamic considerations along with the observation that the centre of the investigated zircon crystal contains monoclinic ZrO2 inclusions. Since the zircon crystals crystallised before the silicate melt spread out into the reactor block basement, the flow of the melt into the basement must also have occurred at temperatures below 1250 °C.